The Administration of Muslim Affairs in the Straits Settlements during the 19th Century - Mansor Majdin, Mohamad Firdaus (IIUM Journal of Religion and Civilisational Studies, 2018)
The Administration of Muslim Affairs in the Straits Settlements during the 19th Century